Dialectics and Implications of Natural Neurotropic Autoantibodies in Neurological Disease and Rehabilitation. Issue 2 (2004) - Poletaev, A. B.; Abrosimova, A. A.; Sokolov, M. A.; Gekht, A. B.; Alferova, V. V.; Gusev, E. I.; Nikolaeva, T. Ya.; Selmi, C.
Abstract : The role of natural idiotypic (Id-Abs) and anti-idiotypic (AId-Abs) autoantibodies against neuro-antigens observed in different neurological disorders is not fully understood. In particular, limited experimental evidence has been provided concerning the qualitative and quantitative serological response after acute injuries of the central nervous system or during chronic mental diseases. In this study, we analyzed the specific Id-Abs and AId-Abs serological reactivities against 4 neuro-antigens in a large population of patients with ischemic stroke, schizophrenia, as well as healthy individuals. Patients with ischemic stroke were tested at different time points following the acute stroke episode and a correlation was attempted between autoantibodies response and different patterns of functional recovery. Results showed variable and detectable Id-Abs and AId-Abs in different proportions of all three populations of subjects. Among patients with different functional recovery after ischemic stroke, a difference in time-related trends of Id-Abs and AId-Abs was encountered. Our observations suggest that changes in the production of natural neurotropic Abs may engender a positive homeostatic, beside a possible pathogenic effect, in specific neurological disorders.